1998
DOI: 10.1021/jp981218z
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Sulfur Headgroups in 4-Mercaptopyridine Self-Assembled Monolayers on Au(111) Studied by Scanning Tunneling Microscopy

Abstract: The structure of self-assembled monolayers of 4-mercaptopyridine on Au(111) has been investigated in perchloric acid solutions by in situ scanning tunneling microscopy (STM). The adsorption of this molecule yields an ordered striped structure with a rectangular (5 × ) unit cell in the double-layer potential range. The sulfur headgroup and pyridine ring moiety of the molecule were clearly imaged. The molecular image is greatly different from that reported previously. The spacing between sulfur headgroups of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
90
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 27 publications
10
90
1
2
Order By: Relevance
“…[9][10][11][12][13][14][15][16] For example, 4-pyridinethiol (4-PySH), which is a popular molecule for use as a modifier, has been studied not only as an electron-transfer promoter for cytochrome c, 9,10 but also from the perspective of fundamental and structural chemistry using surface-sensitive techniques, such as surface-enhanced Raman spectroscopy (SERS), [17][18][19] surface enhanced infrared absorption spectroscopy (SEIRAS), [20][21][22] and scanning tunneling microscopy (STM). [23][24][25][26][27][28][29] 3-Pyridinethiol (3-PySH), which is a structural isomer of 4-PySH, is also expected to be a good modifier for the electron transfer of cytochrome c. Our preliminary results regarding an EC-STM structural investigation of 3-PySH SAM in an acidic solution were almost identical to those for 4-PySH SAM. To elucidate the differences in the surface functionalities of 3-PySH and 4-PySH SAMs, further structural analysis is needed to determine the molecular orientation.…”
Section: Introductionsupporting
confidence: 61%
“…[9][10][11][12][13][14][15][16] For example, 4-pyridinethiol (4-PySH), which is a popular molecule for use as a modifier, has been studied not only as an electron-transfer promoter for cytochrome c, 9,10 but also from the perspective of fundamental and structural chemistry using surface-sensitive techniques, such as surface-enhanced Raman spectroscopy (SERS), [17][18][19] surface enhanced infrared absorption spectroscopy (SEIRAS), [20][21][22] and scanning tunneling microscopy (STM). [23][24][25][26][27][28][29] 3-Pyridinethiol (3-PySH), which is a structural isomer of 4-PySH, is also expected to be a good modifier for the electron transfer of cytochrome c. Our preliminary results regarding an EC-STM structural investigation of 3-PySH SAM in an acidic solution were almost identical to those for 4-PySH SAM. To elucidate the differences in the surface functionalities of 3-PySH and 4-PySH SAMs, further structural analysis is needed to determine the molecular orientation.…”
Section: Introductionsupporting
confidence: 61%
“…24,25 Another possible suggestion for the small intermolecular distances is the sulfur-sulfur dimerization at thiolate headgroups. 27,55 The dimerization at the sulfur headgroups for the decanethiol 55 and 4-mercaptopyridine 27 SAMs on Au(111) led to a sulfur-sulfur spacing of 0.21-0.22 nm. We suggest that at potentials negative of 0.3 V, a decrease of the interaction between 4-MBT and the substrate could drive the thiolate headgroups to form weak dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Studies featuring scanning tunnelling microscopy (STM) have reported √ 3 × 1 [24,25], √ 3 × 5 [26,27], √ 3 × 7 [25] and √ 3 × 10 [24] overlayers under different electrochemical conditions. However, given the difficulties in calibrating the STM measurements for such SAMs on metal substrates, even additional structures might be possible [21,22].…”
Section: Introductionmentioning
confidence: 99%